Peningkatan Kedisiplinan Anak SMK melalui Pembinaan Tanggung Jawab di Panti Asuhan Yatim Piatu Al-Ikhwaniyah, Jurang Mangu Barat, Tangerang Selatan - Safira, Laela; Fadilla, Rifa; Rizky Kamila , Haura; Rizka Akbar, Irfan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstract. Discipline is one of the important aspects in character formation and educational success, especially for vocational high school (SMK) age children who are in the transition period to adulthood and the world of work. At the Al Ikhwaniyah Orphanage, Jurang Mangu Barat, South Tangerang, discipline is still a significant challenge for some students, especially in terms of personal and social responsibility. This paper aims to examine and analyze how training responsibilities can be used as an effective strategy to improve the discipline of vocational school children living and studying in the orphanage. The research method used is qualitative research with a descriptive analysis approach, where data is collected through observation, interviews, and documentation of vocational school children, orphanage administrators, and educators involved in the coaching process. The main focus of this study is to assess changes in children's discipline attitudes before and after the implementation of the responsibility coaching program, which includes the division of daily tasks, involvement in the management of orphanage activities, and the development of awareness through the ethics of routine activities and moral mentoring Keywords: Discipline, Responsibility, Education.